The Perceptions of Overweight and Obese Individuals Regarding Weight-Loss Dietary Supplement Advertisements: A Pilot Cross-Sectional Survey - Nik Nur Anis Ilyany Zamzuri; Nor Elyzatul Akma Hamdan; Nurul Ashikin Jamludin; Mohammad Suhaidi Shaari; Nur Syazwani Taridi; Mohd Shahezwan Abd Wahab; Janattul Ain Jamal (Journal of Public Health and Pharmacy)
Introduction: The negative health consequences of overweight and obesity underscore the importance of weight loss in mitigating these issues. Weight-loss dietary supplements (DS) are highly sought-after by overweight or obese individuals, with widespread advertisements promoting their use. This study aimed to investigate the perceptions of overweight and obese individuals regarding weight-loss DS advertisements.